2017
DOI: 10.1111/infa.12222
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a Communicative Partner: Infant Contingent Responsiveness to Maternal Language and Gestures

Abstract: Infant contingent responsiveness to maternal language and gestures was examined in 190 Mexican American, Dominican American, and African American infant–mother dyads when infants were 14 and 24 months. Dyads were video‐recorded during book‐sharing and play. Videos were coded for the timing of infants’ vocalizations and gestures and mothers’ referential language (i.e., statements that inform infants about objects and events in the world; e.g., “That's a big doggy!”), regulatory language (i.e., statements that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 70 publications
0
28
0
5
Order By: Relevance
“…In support, a correlational study (Miller & Gros‐Louis, ) showed that caregiver responses that did not follow in on the attentional focus of infants aged 13–16 months reduced infants’ concurrent frequency of gestures and gesture‐vocal combinations. Another study showed that infants were more likely to gesture when mothers responded to their gestures with referential language while they were less likely to gesture when mothers responded with regulatory language (Kuchirko, Tafuro, & Tamis‐LeMonda, ). Likewise, caregivers’ comments or actions on objects other than the target of infants’ points at 10–13 months were negatively related with the improvement in infants’ gesture scores from 10–13 to 15 months as measured by the MCDI questionnaire (Wu & Gros‐Louis, ).…”
Section: Factors Influencing the Development Of Pointing Frequencymentioning
confidence: 99%
“…In support, a correlational study (Miller & Gros‐Louis, ) showed that caregiver responses that did not follow in on the attentional focus of infants aged 13–16 months reduced infants’ concurrent frequency of gestures and gesture‐vocal combinations. Another study showed that infants were more likely to gesture when mothers responded to their gestures with referential language while they were less likely to gesture when mothers responded with regulatory language (Kuchirko, Tafuro, & Tamis‐LeMonda, ). Likewise, caregivers’ comments or actions on objects other than the target of infants’ points at 10–13 months were negatively related with the improvement in infants’ gesture scores from 10–13 to 15 months as measured by the MCDI questionnaire (Wu & Gros‐Louis, ).…”
Section: Factors Influencing the Development Of Pointing Frequencymentioning
confidence: 99%
“…Specifically, we assessed how opposing signal‐to‐noise ratios of contingent sensitive and redirective responding among caregivers correspond to differences in infants’ attentional preferences toward socially relevant stimuli, as well as infants’ general attention span and reactivity to caregivers’ social prompts. Although all infants spent the majority of their time looking at objects, infants of highly sensitive caregivers showed attention patterns that imply social attunement (Kuchirko et al., ). This attunement was apparent within these infants’ looking preferences as well as the timing of their gaze shifts, which accommodated the content of their caregivers’ responses.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, our results taken together indicate that infants of highly sensitive caregivers may be more selectively attuned to their caregivers’ social cues than infants of highly redirective caregivers. Such selectivity may be a precursor to the specificity of vocal, gestural, and affective responding that older infants exhibit during communicative exchanges with adults (e.g., Beebe et al., ; Kuchirko et al., ), though further longitudinal research is needed to explore this possibility further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, interactive contexts are characterized as situations that provide learning and development due to symbolic mediation; therefore, "the path from object to child and from child to object passes through another person" (Vygotsky, 2007, p. 20). It is also noteworthy to point out the interinfluence during social exchanges where child is considered an active participant (Kuchirko, Tafuro, & Tamis-LeMonda, 2017;Martins & Monteiro, 2017;Salomão, 2010).…”
mentioning
confidence: 99%